Cultural and Social Influences on Hadith Classification: An Analytical Study of Historical Transformations - Abdulrahman, Mohammed Adnan (Journal of Ecohumanism, 2024)
This thesis studies the historical development and current dilemma of Hadith classification, with particular attention to the impact of cultural, social and political factors. It examines how classical scholars like Imam Bukhari and Imam Muslim developed the standards for authenticating Hadith, such that rigorous criteria to this day inform much of contemporary scholarship. The impact of regional cultures on the Hadith interpretation, as well as the methods of classification by different Islamic schools of thought are also pointed out by the study. Furthermore, fundamental irony in the integrity of Hadith studies in the times of globalization, digital media and intercultural exchange is the rise of the new challenges for the contemporary methods of Hadith studies by modern scholars, balancing the modern tools and perspectives with the traditional one. By digital, interdisciplinary approach, and awareness of cultural and social contexts, such authenticity can be preserved during preservation of Hadith. Finally, the paper concludes by suggesting to scholars how to adapt to the current challenges by respecting the most rigorous standards but allowing new methodologies and promoting intercultural dialogue. This study highlights the fluid nature of Hadith classification and cautions against an oversimplification of the traditions of scholarship that relies on a rigid interpretation of the rules of classification in the present world.